2022
DOI: 10.3390/ijerph19127250
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Toxigenic Fungi in Livestock and Poultry Feedstuffs

Abstract: The purpose of this study was to discover how abundant toxigenic fungi and mycotoxins are in animal feedstuff samples. A total of ninety samples representing various types of animal feedstuff samples were collected from ninety sites in Egypt. Isolation, identification, and determination of mycotoxins (aflatoxins B1, B2, G1, G2, and ochratoxin A) were performed. The results revealed that 79 (87.77%) of the samples were contaminated with fungi, and 1.1 × 105 CFU/g were recovered, including 41 fungal species belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…In poultry farming, fungi play an important role in the decomposition of organic matter present in poultry waste, such as food remains and bird excrement. They help in recycling nutrients and maintaining ecological balance [ 7 ]. However, some species of fungi can produce mycotoxins, substances that are toxic to animals when feed and food are contaminated.…”
Section: Fungi and Poultry Farmingmentioning
confidence: 99%
See 1 more Smart Citation
“…In poultry farming, fungi play an important role in the decomposition of organic matter present in poultry waste, such as food remains and bird excrement. They help in recycling nutrients and maintaining ecological balance [ 7 ]. However, some species of fungi can produce mycotoxins, substances that are toxic to animals when feed and food are contaminated.…”
Section: Fungi and Poultry Farmingmentioning
confidence: 99%
“…Fungal presence in poultry farms generates organic dust composed of various particles, including fungal spores, some of which can cause allergies, posing health risks to workers [ 7 ]. The article also discusses the vital role of fungi in maintaining ecological balance and their interactions with xenobiotics, foreign chemical substances in the body, with applications in bioremediation.…”
Section: Introductionmentioning
confidence: 99%
“…More seriously, AFB1 levels were as high as 39.9 μg/kg in Pakistan [ 11 ], where 100% of grower broiler feed was contaminated with AFB1 [ 12 ]. In Egypt, it was observed that AFB1 and aflatoxin B2 (AFB2) were both present in animal feedstuff ranging from 0.851 to 1.363 µg/kg [ 13 ]. Even, AFB1 concentrations of 1067 µg/kg have been reported in poultry feed in West Africa, highlighting the widespread presence of AFs in feed commodities [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It should be emphasized that mycotoxins in the litter can have two main origins ( Figure 1 ): (i) mycotoxins can accumulate in the feed during the cultivation, harvesting, transportation, and storage of the feedstock [ 22 ] and (ii) mycotoxins appear as a result of litter contamination by microscopic fungi during its transportation and storage due to high content of proteins, moisture, etc. [ 23 ].…”
Section: Introductionmentioning
confidence: 99%